2020
DOI: 10.1007/s11694-020-00579-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of varieties, curing of tubers and extraction methods on functional characteristics of potato starch

Abstract: The investigation was conducted to study the effects of variations in quality and functional properties of starch isolated from fresh and cured tubers of potato, different varieties and extraction methods. The starch was extracted from four white flesh varieties (Kufri Chipsona-4, Kufri Badshah, Kufri Pushkar, Kufri Bahar) and one pink flesh variety (Kufri Sindhuri). Among the different starch extraction methods tried, the results have been reported for water extraction method (control) and combined method (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…15 The paste clarity, however, has been reported to be negatively correlated with amylose content. 21 Similarly, in the present investigation also, TPM had less amylose and more PC than APM (Table 1). Aristizabal and Sańchez in 2007 13 indicate that reference values for paste clarity (PC) in starches vary between 12.5% and 95% and starch pastes, with a transmittance lower than 40%, are considered opaque or turbid (Table 3).…”
Section: Morphological Propertiessupporting
confidence: 80%
See 1 more Smart Citation
“…15 The paste clarity, however, has been reported to be negatively correlated with amylose content. 21 Similarly, in the present investigation also, TPM had less amylose and more PC than APM (Table 1). Aristizabal and Sańchez in 2007 13 indicate that reference values for paste clarity (PC) in starches vary between 12.5% and 95% and starch pastes, with a transmittance lower than 40%, are considered opaque or turbid (Table 3).…”
Section: Morphological Propertiessupporting
confidence: 80%
“…It has earlier been reported that different extraction techniques, potato varieties, storage conditions, and packaging affect structural and composition of potato starch, which also significantly impacted its WAI, WSI, SP, and syneresis . The paste clarity, however, has been reported to be negatively correlated with amylose content . Similarly, in the present investigation also, TPM had less amylose and more PC than APM (Table ).…”
Section: Resultssupporting
confidence: 65%
“…The determination of freeze-thaw stability was based on the method of Phogat et al 24) . The dehydration ratio is the ratio of the water separated in the centrifuge tube to the weight of the original gel.…”
Section: Freeze-thaw Stabilitymentioning
confidence: 99%
“…The protein, ash, and lipid contents of starches obtained from eight Korean sweet potato varieties varied between 0.01 and 0.28%, 0.10 and 0.12%, and 0.04 and 0.16%, respectively, with the Jeungmi and Shinwhangmi starches having significantly higher protein contents but Shinwhangimi and Shinyulmi having lower lipid contents than other sweet potato varieties [12]. Phogat et al [14] reported that starch isolated from the potato variety Kufri Chipsona-4 showed the highest yield, water absorption capacity (WAC) (258%), swelling power (SP) (38.4 g/g), and solubility (35.8%) compared to other varieties. Tessema and Admassu [17] reported that the starch yield isolated by the sodium metabisulphite (SMS) (0.075% w/v) method was significantly the highest (75.56%, db) compared with the sodium chloride (NaCl) and distilled water (DW) methods, with different concentrations from the anchote tuber.…”
Section: Introductionmentioning
confidence: 99%
“…The application of starches from underutilized tubers like EP requires an in-depth characterization of their physicochemical properties and the selection of a suitable starch extraction method. Studies have shown that variations in the tuber variety or ecotype [12][13][14] and the isolation methods used [14][15][16][17][18] to separate starch from tubers can have an impact on the starch yield and physicochemical, functional, and structural characteristics of starches. The protein, ash, and lipid contents of starches obtained from eight Korean sweet potato varieties varied between 0.01 and 0.28%, 0.10 and 0.12%, and 0.04 and 0.16%, respectively, with the Jeungmi and Shinwhangmi starches having significantly higher protein contents but Shinwhangimi and Shinyulmi having lower lipid contents than other sweet potato varieties [12].…”
Section: Introductionmentioning
confidence: 99%